A Multimodal Approach in Project Based Learning to Enhance Critical Thinking Skills in Physics Instruction : A Systematic Literature Review - Yasfi Ismayani; Tiara Dwi Saiva (Indonesian, 2023)
This study aims to analyze the effectiveness of a multimodal approach in Project Based Learning (PjBL) on students’ critical thinking skills in physics learning. The research employed a Systematic Literature Review (SLR) method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Data were collected from Google Scholar with a publication range from 2014 to 2023, resulting in 10 articles that met the inclusion criteria. The data were analyzed using qualitative descriptive techniques through categorization, comparison, and synthesis of findings. The results indicate that PjBL consistently improves students’ critical thinking skills through project-based learning activities involving problem identification, planning, implementation, and evaluation. In addition, the multimodal approach enhances physics concept understanding through various representations such as visual, textual, and digital media. The integration of PjBL and multimodal learning provides a more optimal effect in improving student engagement and critical thinking skills. Therefore, this approach can be considered an effective learning strategy for 21st-century physics education.